(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: It is a pigmentation disorder in which melanocytes (the cells that make pigment) in the skin are destroyed. As a result, white patches appear in the skin in different parts of the body. Objective: The objective of this study is to see the efficacy of systemic PUVA in the treatment of vitiligo patient. Methods: This is an prospective longitudinal interventional study, carried out in the depigmented area was assessed according to the department of Dermatology and Venereology, Combined Military Hospital, Dhaka in between the duration of April 2010 to March 2011. Total 25 vitiligo patients based on inclusion criteria like patient with vitiligo affecting more than 5% body surface area, patient having ivory- white fluorescence on Woods lamp, patient who was above 15 years of age, patient who had given written consent, patient was not taken any previous treatment etc. Results: This study showed the therapeutic response of study group after 04 weeks of therapy, 05 (20%) patients responsed Fair, 15 (60%) patients responsed Poor and no responsed by 05 (20%) patients. Therapeutic response of study group after 08 weeks of therapy showed that 15 (60%) patients responsed Fair and 10 (40%) patients responsed Poor. It was observed after 12 weeks of therapy that 13 (52%) patients responsed Poor followed by 10 (40%) patients responsed Fair and 02 (08%) patients responsed well. 29 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Therapeutic response of study group after 16 weeks of therapy was 15 (60%) patients responsed Fair, followed by 06 (24%) patients responsed Poor and 04 (16%) patients responsed Good. It was showed that after 20 weeks of therapy 13 (52%) patients responsed Fair, followed by 08 (32%) patients responsed Good, 03 (12%) patients responsed Poor and 01 (04%) patients responsed Excellent. It was observed that after 24 weeks of therapy 12 (48%) patients responsed Good, followed by 08 (32%) patients responsed Fair, 03 (12%) patients responsed Poor and 02 (08%) patients responsed Excellent. Conclusion: Systemic PUVA for the repigmentation of vitiligo seems to be effective. Study needs large number of patients for longer period of duration for confirmation of results. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22900 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014